From Evidence to Practice: Are Low-Risk Breast Cancer Patients still Enduring Unnecessary Costs of Radiation?. Issue 12 (December 2019) - Thornhill, Rosanne; Chang, Jenny; Selleck, Matthew; Senthil, Maheswari; Solomon, Naveen; Namm, Jukes P.; Garberoglio, Carlos A.; Lum, Sharon
Radiation is routinely recommended after conservative surgery for breast cancer, despite longstanding Level I evidence showing no survival benefit for elderly patients with favorable disease using endocrine therapy. We sought to evaluate radiation use and costs in patients eligible for omission of radiation. A retrospective single-institution review from 2005 to 2017 was performed of women aged ≥70 years, with cT1N0M0, who were ER/PR positive and HER-2 negative, and receiving breast-conserving surgery. Patient, tumor, and treatment characteristics were compared by use of radiation. Cost estimates used Medicare's 2019 fee schedule. Of 84 patients meeting the study criteria, 72.6 per cent received radiation and 56 per cent received endocrine therapy, with four recurrences (4.9% radiated and 4.4% not radiated, P = 0.9). Early and late grade I radiation toxicities occurred in 67.2 per cent and 26.2 per cent of radiated patients, respectively. Younger age ( P = 0.01), receipt of endocrine therapy ( P < 0.0001), and axillary surgery ( P < 0.0001) were significantly associated with radiation use. There were no significant differences in radiation use based on race/ethnicity, language, comorbidities, BMI, or pathologic tumor size. Estimated total radiation cost was 646, 426. Radiation remains overused and endocrine therapy, underused in breast cancer patients eligible to avoid radiation. As gatekeepers for radiation oncology referrals, surgeons can diminish both physical and financial costs of radiation in eligible patients.